Electroreductive coupling of 2-acylbenzoates with α,β-unsaturated carbonyl compounds: density functional theory study on product selectivity - Kise, Naoki; Sakurai, Toshihiko (Beilstein Journal of Organic Chemistry, 2022)
The electroreductive coupling of 2-acylbenzoates with acrylonitrile in the presence of TMSCl and successive treatment with 1 M HCl gave 2-cyanonaphthalen-1-ols or 3-(3-cyanoethyl)phthalides. On the other hand, the reaction of 2-acylbenzoates with methyl vinyl ketone under the same conditions produced 3-(3-oxobutyl)phthalides as the sole products. What determines the product selectivity was studied using DFT calculations.
Keywords: 2-acylbenzoates; chlorotrimethylsilane; 3-(3-cyanoethyl)phthalides; 2-cyanonaphthalen-1-ols; electroductive coupling

(untitled) - Little, R. D. (J. Org. Chem., 2020)

(untitled) - Waldvogel, S. R.; Lips, S.; Selt, M.; Riehl, B.; Kampf, C. J. (Chem. Rev., 2018)

(untitled) - Jiang, Y.; Xu, K.; Zeng, C. (Chem. Rev., 2018)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Kise, N.; Yamamoto, S.; Sakurai, T. (J. Org. Chem., 2020)

(untitled) - Kise, N.; Manto, T.; Sakurai, T. (J. Org. Chem., 2021)

(untitled) - He, M.-X.; Mo, Z.-Y.; Wang, Z.-Q.; Cheng, S.-Y.; Xie, R.-R.; Tang, H.-T.; Pan, Y.-M. (Org. Lett., 2020)

(untitled) - Zhang, W.; Li, T.; Wang, Q.; Zhao, W. (Adv. Synth. Catal., 2019)

(untitled) - Zhou, C.; Fang, F.; Cheng, Y.; Li, Y.; Liu, H.; Zhou, Y. (Adv. Synth. Catal., 2018)

(untitled) - Beck, J. J.; Chou, S.-C. (J. Nat. Prod., 2007)

(untitled) - Karmakar, R.; Pahari, P.; Mal, D. (Chem. Rev., 2014)

(untitled) - Li, S.; Su, M.; Sun, J.; Hu, K.; Jin, J. (Org. Lett., 2021)

(untitled) - Jia, B.; Yang, Y.; Jin, X.; Mao, G.; Wang, C. (Org. Lett., 2019)

(untitled) - Anselmo, M.; Basso, A.; Protti, S.; Ravelli, D. (ACS Catal., 2019)

(untitled) - Miura, H.; Terajima, S.; Shishido, T. (ACS Catal., 2018)

(untitled) - Zhang, S.; Li, L.; Wang, H.; Li, Q.; Liu, W.; Xu, K.; Zeng, C. (Org. Lett., 2018)

(untitled) - Greszler, S. N.; Johnson, J. S. (Angew. Chem., Int. Ed., 2009)

(untitled) - Zhang, H.; Zhang, S.; Liu, L.; Luo, G.; Duan, W.; Wang, W. (J. Org. Chem., 2010)

(untitled) - Che, C.; Xiang, J.; Wang, G.-X.; Fathi, R.; Quan, J.-M.; Yang, Z. (J. Comb. Chem., 2007)

(untitled) - Bisai, V.; Suneja, A.; Singh, V. K. (Angew. Chem., Int. Ed., 2014)

(untitled) - He, Y.; Cheng, C.; Chen, B.; Duan, K.; Zhuang, Y.; Yuan, B.; Zhang, M.; Zhou, Y.; Zhou, Z.; Su, Y.-J.; Cao, R.; Qiu, L. (Org. Lett., 2014)

(untitled) - Betterley, N. M.; Kerdphon, S.; Chaturonrutsamee, S.; Kongsriprapan, S.; Surawatanawong, P.; Soorukram, D.; Pohmakotr, M.; Andersson, P. G.; Reutrakul, V.; Kuhakarn, C. (Asian J. Org. Chem., 2018)

(untitled) - Broom, N. J. P.; Sammes, P. G. (J. Chem. Soc., Perkin Trans. 1, 1981)